Management of Egg-Bound Syndrome in an Aseel Cross Hen by Digital Milking Method: A Case Report - Banoth, Vennela; Gupta, Chhavi; Akambaram, Sabarinathan; Ramasamy, Rajkumar; Ganesan (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Egg is formed gradually in the different parts of hen’s reproductive system taking about 24 h (Hasan and Khaliduzzaman, 2022). In egg bound syndrome a fully or partially formed egg is lodged in the shell gland (uterus) or vagina, but cannot be expelled by the bird at a normal rate (Srinivasan et al., 2014; Muthulakshmi et al., 2015). Chaurasia et al. (2024) reported egg binding is a condition characterized by the inability of an egg to pass through the cloaca within the normal timeframe, leading to difficulty in laying leading a condition known as dystocia in hens. Hosotani et al. (2023) stated fatigued muscular peristalsis in the oviducts owing to hypocalcemia, stress, aging, overweight, systemic illness and abnormalities in the oviductal ciliated epithelium are linked to internal laying and egg-bound syndrome in hens along with reduced quality of egg component also alters the oviductal transportation efficiency. Egg bound syndrome is commonly noticed in pet birds and broiler breeders (Eitan and Soller, 2009) resulting in life threatening symptoms and high mortality in the present report.